Definitional Patterns in Specialized Resources for Schoolchildren - Ostroški Anić, Ana (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
The paper describes the analysis of frequent definitional patterns in two specialized corpora, English and Croatian, compiled of educational texts in the field of climate change written for schoolchildren and young adults. The analysis is based on extracting knowledge- rich contexts from the corpora, followed by determining common lexical markers used to identify definitions, lexical knowledge patterns, and lexical-semantic relations between terms. Definitions and definitional patterns will be used in developing a children- oriented dictionary of climate change in Croatian.